Controls on CO2 storage security in natural reservoirs and implications for CO2 storage site selection. (August 2016) - Miocic, Johannes M.; Gilfillan, Stuart M.V.; Roberts, Jennifer J.; Edlmann, Katriona; McDermott, Christopher I.; Haszeldine, R. Stuart
Highlights: The to date most comprehensive analysis of naturally occurring CO2 reservoirs. CO2 retention is controlled by reservoir depth, CO2 density & state, caprock integrity. Migration to the surface occurs along faults and fracture zones. New storage site selection criteria proposed, based on secure natural reservoirs. Abstract: For carbon capture and storage to successfully contribute to climate mitigation efforts, the captured and stored CO2 must be securely isolated from the atmosphere and oceans for a minimum of 10, 000 years. As it is not possible to undertake experiments over such timescales, here we investigate natural occurrences of CO2, trapped for 10 4 –10 6  yr to understand the geologic controls on long term storage performance. We present the most comprehensive natural CO2 reservoir dataset compiled to date, containing 76 naturally occurring natural CO2 stores, located in a range of geological environments around the world. We use this dataset to perform a critical analysis of the controls on long-term CO2 retention in the subsurface. We find no evidence of measureable CO2 migration at 66 sites and hence use these sites as examples of secure CO2 retention over geological timescales. We find unequivocal evidence of CO2 migration to the Earth's surface at only 6 sites, with inconclusive evidence of migration at 4 reservoirs. Our analysis shows that successful CO2 retention is controlled by: thick and multiple caprocks, reservoir depths of >1200 m, and high density CO2 . Where CO2 has migrated to surface, the pathways by which it has done so are focused along faults, illustrating that CO2 migration via faults is the biggest risk to secure storage. However, we also find that many naturally occurring CO2 reservoirs are fault bound illustrating that faults can also securely retain CO2 over geological timescales. Hence, we conclude that the sealing ability of fault or damage zones to CO2 must be fully characterised during the appraisal process to fully assess the risk of CO2 migration they pose. We propose new engineered storage site selection criteria informed directly from on our observations from naturally occurring CO2 reservoirs. These criteria are similar to, but more prescriptive than, existing best-practise guidance for selecting sites for engineered CO2 storage and we believe that if adopted will increase CO2 storage security in engineered CO2 stores.